Maria Grazia (Maria Grazia Francia) stands with one hand holding the end of her head scarf - De Santis, Giuseppe, 1917-1997 (Z. Smith Reynolds Library, Wake Forest University, 1950)
This film is a moralistic tale of the privileged and underprivileged, in which shepherds break out of their cycle of fatalism and resignation.Patterned on a folk tale, the characters are divided into good and bad types.
Keywords: Motion picture actors and actresses -- Italy; Stills (motion pictures); Shepherds -- Italy -- Drama; Motion picture producers and directors -- Italy; Motion pictures -- Italy -- History -- Sources; Italy -- Social life and customs -- 1945--- Drama